2017
DOI: 10.1038/s41467-017-00450-6
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Akt activation drives acquired EGFR inhibitor resistance in lung cancer

Abstract: Non-small-cell lung cancer patients with activating epidermal growth factor receptor (EGFR) mutations typically benefit from EGFR tyrosine kinase inhibitor treatment. However, virtually all patients succumb to acquired EGFR tyrosine kinase inhibitor resistance that occurs via diverse mechanisms. The diversity and unpredictability of EGFR tyrosine kinase inhibitor resistance mechanisms presents a challenge for developing new treatments to overcome EGFR tyrosine kinase inhibitor resistance. Here, we show that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 51 publications
(56 reference statements)
8
113
0
Order By: Relevance
“…Our data suggest that activation of the PI3K/AKT pathway may be an important compensation mechanism for tumor cell survival after EGFR loss. In agreement with our findings, a recent study showed that Akt activation drives acquired resistance to EGFR-TKI 31 . However, our study further revealed that activated Akt induced by EGFR ablation can be further decreased by elortinib treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Our data suggest that activation of the PI3K/AKT pathway may be an important compensation mechanism for tumor cell survival after EGFR loss. In agreement with our findings, a recent study showed that Akt activation drives acquired resistance to EGFR-TKI 31 . However, our study further revealed that activated Akt induced by EGFR ablation can be further decreased by elortinib treatment.…”
Section: Discussionsupporting
confidence: 93%
“…This has led to the development of second-and thirdgeneration irreversible EGFR-TKIs that have also shown outstanding clinical efficacy. Yet studies have shown that cancer cells (and patients) ultimately acquire resistance to these second-and third-generation irreversible EGFR-TKIs, either via acquisition of novel EGFR mutations (C797, L792, or L718) or through bypassing receptor tyrosine kinase signaling by means of a mutation in BRAF or the activation of IGF1R (insulin-like growth factor receptor 1), SRC (SRC protooncogene, nonreceptor tyrosine kinase), FAK/PTK2 (protein tyrosine kinase 2), and YAP (YY1-associated protein 1), which are similar to resistance mechanisms discovered in first-generation EGFR-TKIs (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Thus, it is important to investigate and understand resistance ABBREVIATIONS: AKR, aldo-keto reductase; ARE, antioxidant-responsive element; CI, combination index; ECM, extracellular matrix; EGFR, epidermal growth factor receptor; EV, empty vector; FACS, fluorescence-activated cell sorting; GR, gefitinib-resistant; IC 50 , half-maximal inhibitory concentration; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; NSCLC, non-small cell lung cancer; qRT-PCR, quantitative RT-PCR; TKI, tyrosine kinase receptor mechanisms in EGFR-TKI therapy.…”
mentioning
confidence: 86%
“…The importance of Akt activation may also relate to the development of resistance to therapy. Preclinical evidence suggests that Akt activation may confer acquired resistance to EGFR inhibitors in EGFR mutant NSCLC . Similarly mTOR activation has been associated with EGFR and KRAS mutations and may act as a mechanism of resistance to EGFR inhibitors .…”
Section: Importance Of the Pi3k/akt/mtor Pathway In Nsclcmentioning
confidence: 99%
“…Preclinical evidence suggests that Akt activation may confer acquired resistance to EGFR inhibitors in EGFR mutant NSCLC. 59 Similarly mTOR activation has been associated with EGFR and KRAS mutations and may act as a mechanism of resistance to EGFR inhibitors. 60 Given the encompassing downstream signaling effects of the PI3K/Akt/mTOR pathway on the development and progression of malignancy, and its potential influence in response and resistance to standard therapies, it represents an attractive target for anticancer therapy in NSCLC.…”
Section: Importance Of the Pi3k/akt/mtor Pathway In Nsclcmentioning
confidence: 99%